1992
DOI: 10.1002/masy.19920540105
|View full text |Cite
|
Sign up to set email alerts
|

New synthetic routes towards polyphosphazenes

Abstract: A b s t r a c t : Two new methods for the synthesis of polyphosphazenes are described. The first is based on the catalyzed polycondensation of phosphoranimines using various catalysts and initiators. Certain mechanistic aspects of this process with reactive intermediates are discussed. Linear polymers are formed quantitatively at temperatures around 100 OC in a few hours (the thermal process requires a few days at 200 OC). The second method is based on the direct reaction between phosphonites and phosphinites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The growing polymer chains remained active after all the initial monomer 8 had been consumed. A sample of [NdPMe(Et)] n (8) was prepared via the reaction of 1 with PCl 5 in a 40:1 ratio under conditions where all the phosphoranimine had been converted to polymer, as determined by 1 H and 31 P NMR spectroscopy. A portion of this mixture was shown by GPC to have an M n ) 1.1 × 10 4 and PDI ) 1.09.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The growing polymer chains remained active after all the initial monomer 8 had been consumed. A sample of [NdPMe(Et)] n (8) was prepared via the reaction of 1 with PCl 5 in a 40:1 ratio under conditions where all the phosphoranimine had been converted to polymer, as determined by 1 H and 31 P NMR spectroscopy. A portion of this mixture was shown by GPC to have an M n ) 1.1 × 10 4 and PDI ) 1.09.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7] This polymerization proceeds at temperatures near 180-200 °C, to produce a range of poly(aryl/alkylphosphazenes) with molecular weights (M n ) which approach 1 × 10 5 and with polydispersity indices (PDI) of 1.5-3.0. In addition, Matyjaszewski and co-workers have demonstrated that phosphoranimines, such as (CF 3 CH 2 O) 3 PdNSiMe 3 , undergo both anionic 8,9 and cationic 10 CF 3 ) 2 ] n with molecular weights of (1.0-5.0) × 10 4 and with a wide range of polydispersities (1. 3-2.5).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor yields of soluble polymer have proved a major limitation for the commercialization of polyphosphazenes. Thus, alternative, non-ROP, routes have also been investigated [164][165][166][167], albeit with, as yet, limited commercial success. Almost one hundred years after polyphosphazenes were first documented, Allcock's group showed how to convert the base polymer into useful materials (see, e.g., Reference [168]).…”
Section: Ring-opening Polymerization Of Phosphazenesmentioning
confidence: 99%
“…The first catalyzed/initiated polymerization of a phosphoranimine monomer by fluoride ion was previously reported ( Scheme 1 a) and then extensively investigated [ 33 ]. The successful conversion of these monomers to polyphosphazenes initiated/catalyzed by fluoride anion, trifluoroethoxide anion, and N -methylimidazole was described [ 34 , 35 , 36 ]. Polyphosphazene random and block copolymers with mixed alkoxy/alkoxyether substituents were subsequently prepared by the fluoride/anionic method and characterized [ 37 ].…”
Section: Introductionmentioning
confidence: 99%